PARTISIPASI ANGGOTA IKATAN ALUMNI MAGANG JEPANG TERHADAP KELEMBAGAAN PETANI - Ahmad Syariful Jamil; Annisa Fitri; Hidayat Hidayat; Fadila Marga Saty (Universitas Galuh Ciamis, 2021)
Farmer institutions are places where people gather to channel their aspirations, opinions, and tools to fulfill their basic needs. The purpose of this study was to analyze the characteristics and the participation of members of the Japanese internship alumni association to the farmer institution. This research was conducted from September 2020 to March 2021. The respondents were determined as many as 50 alumni by purposive sampling ranging fromWest Java, Central Java to East Java Provinces. The data analysis used was descriptive qualitative method. The results showed that the characteristics of the members of the Japanese internship alumni association in general were relatively young, had relatively high formal and informal education, and most of their businesses had well developed. The participation of members of the Japanese internship alumni association to participate in the farmer institution was 94%. In addition, most of the Japanese alumni had a role as committee members in the farmers institution, 68%, and had been involved for a relatively long time in the farmer institution. The involvement of alumni in agricultural institutions for more than 10 years. One of the reasons for Japanese internship alumni to join the institution was to help gain access to knowledge and technology. This indicates that alumni had a high level of awareness of the strategic role of farmer institutions in advancing their business.